2020
DOI: 10.2334/josnusd.18-0468
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of TRPV4 ionotropic channel in tongue mechanical hypersensitivity in dry-tongue rats

Abstract: Although xerostomia can cause persistent oral pain, the mechanisms underlying such pain are not well understood. To evaluate whether a phosphorylated p38 (pp38)-TRPV4 mechanism in trigeminal ganglion (TG) neurons has a role in mechanical hyperalgesia of dry tongue, a rat model of dry tongue was used to study the nocifensive reflex and pp38 and TRPV4 expression in TG neurons. The head-withdrawal reflex threshold for mechanical stimulation of the tongue was significantly lower in dry-tongue rats than in sham rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The pERK-pGluR1 cascade was involved in the central neuronal mechanism of drying tongue pain in the trigeminal spinal nucleus caudalis (Vc). Chen et al [68] studied the peripheral neuronal mechanism in dry mouth model rats and suggested that activation of TRPV4 via pp38 in trigeminal ganglion neurons is involved in mechanical hyperalgesia.…”
Section: A Challenge In Elucidating the Etiology Of Bmsmentioning
confidence: 99%
“…The pERK-pGluR1 cascade was involved in the central neuronal mechanism of drying tongue pain in the trigeminal spinal nucleus caudalis (Vc). Chen et al [68] studied the peripheral neuronal mechanism in dry mouth model rats and suggested that activation of TRPV4 via pp38 in trigeminal ganglion neurons is involved in mechanical hyperalgesia.…”
Section: A Challenge In Elucidating the Etiology Of Bmsmentioning
confidence: 99%
“…TRPV4 is activated by warm temperature (>27 • C) and extracellular osmolarity, indicating its role as a mechanosensitive channel [15]. Peripheral TRPV4 antagonism suppresses xerostomia-induced tongue mechanical allodynia in rodents [16]. In some studies, changes in the TRPV1 and TRPV4 expression in the primary nociceptive neurons following trigeminal nerve injury or orofacial trauma were reported to be involved in orofacial pain hypersensitivity [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…S, seconds. (Hamamoto et al, 2008;Foote et al, 2022), lungs (Fernández-Fernández et al, 2008, cornea (Mergler et al, 2011), esophagus (Mihara et al, 2011;Ueda et al, 2011), stomach (Mihara et al, 2016), bladder (Birder et al, 2007;Janssen et al, 2011), oral mucosa (Nakatsuka and Iwai, 2009;Moayedi et al, 2022;Yahya et al, 2022), odontoblasts (Egbuniwe et al, 2014), taste buds (Matsumoto et al, 2019), hippocampal neurons (Shibasaki et al, 2007), dorsal root ganglia (Cao et al, 2009;Liu et al, 2010;Lechner et al, 2011), trigeminal (Denadai-Souza et al, 2012Chen et al, 2013Chen et al, , 2014Chen et al, , 2020, and vagal ganglia (Bonvini et al, 2016), and nerve fibers in the dental pulp (Bakri et al, 2018). Here we report TRPV4 on nerve fibers in SLN-innervated swallowing-related regions.…”
Section: Discussionmentioning
confidence: 99%
“…Transient receptor potential vanilloid 4 is localized in TG (Denadai-Souza et al, 2012;Chen et al, 2013Chen et al, , 2014Chen et al, , 2020; therefore, we used TG sections as a positive control for the anti-TRPV4 antibody (Supplementary Figure 1). As a negative control, the sections were incubated with a universal negative control reagent (Cat # ADI-950-231-0025; Enzo Life Sciences, Inc., Farmingdale, NY) instead of the primary antibody (Supplementary Figure 1).…”
Section: Immunohistochemical Analysis Of the Npjcmentioning
confidence: 99%